2014
DOI: 10.1016/j.erap.2014.04.004
|View full text |Cite
|
Sign up to set email alerts
|

French validation of the 7-item Game Addiction Scale for adolescents

Abstract: is a short instrument (7-item) for evaluating video game playing by adolescents. Objective.-The aim of the current research was to investigate the psychometric properties of a French version of the 7-item Game Addiction Scale for adolescents. Method.-Two studies were conducted with two samples of French adolescents between the ages of 10 and 18 (study 1: n = 159; study 2: n = 306). First, we examined the factor structure and internal consistency. Second, we added a concurrent validity analysis with estimation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
36
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 38 publications
8
36
0
3
Order By: Relevance
“…13,12 The convergent validity of our scale was found by testing the relation between our IGD questionnaire and the GAS. 15 Results showed that our scale has good convergent validity. Moreover, IGD has similar psychometric properties and similar structural factor to the GAS.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…13,12 The convergent validity of our scale was found by testing the relation between our IGD questionnaire and the GAS. 15 Results showed that our scale has good convergent validity. Moreover, IGD has similar psychometric properties and similar structural factor to the GAS.…”
Section: Discussionmentioning
confidence: 90%
“…The GAS is a French questionnaire measuring game addiction 15 and it was added at the end of the questionnaire to test for convergent validity. This measure is not based on DSM-5 criteria and it is validated only on an adolescent population.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We are not aware of any study that has tested the GAS against the monotonicity assumption, but previous studies have given inconsistent results regarding dimensionality and local independency. Although most studies have found support for a unidimensional factorial structure [8,[17][18][19], this was not the case in a large Norwegian study [20], which found a better fit for a correlated 2-factor structure that distinguished between what they interpreted as core and peripheral criteria items. Earlier work on the French and German validation of the GAS conducted on the present sample found good fit to a unidimensional factor structure, but only after allowing for the correlation of 6 error terms, which suggests some local dependencies.…”
Section: Introductionmentioning
confidence: 78%
“…O artigo original não apresentou a correlação interna dos itens ou dos domí-nios. Há outros manuscritos publicados sobre a avaliação da equivalência semântica e consistência interna da GAS, porém apenas para a versão reduzida, composta por sete itens do instrumento original (em francês 23 , chinês 24 e norueguês 25 ). Os autores da GAS 9 consideram que uma resposta deve ser considerada positiva quando o indivíduo responde 3 (algumas vezes), na variação de 1 (nunca) a 5 (muito frequentemente).…”
Section: Game Addiction Scale (Gas)unclassified